2017
DOI: 10.15640/aijb.v5n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antibacterial and AntifungalMetabolites by (S.albovinaceus) Strain no.10/2 and MediaOptimization

Abstract: A new strain ofActinomycete (S. albovinaceus) no.10/2 with a broad antifungal and antibacterial activitywas isolated from soil sample of Palestine.The medium composition for antibioticproduction fromstrain S.albovinaceus was optimized using shake-flask methodology.The parameters that resulted in maximum antibiotic production are: 1.25 % mannitol and 1 % malt extract were found to be best carbon and nitrogen sources respectively for growth and antifungal and antibacterial production. Similarly initial pH of 7.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The antibiotic biosynthesis of S. cavourensis YBQ59 was observed after 18 h and the antimicrobial activity against MRSE and S. Typhimurium was dramatically increased within 42 h, then slowly increased and reached a peak located between 72 h and 78 h (inhibition zones > 34.0 mm). The antimicrobial activity was stable until 90 h and then slightly decreased after 120 h. Thus, S. cavourensis YBQ59 produced a highest yield of antibiotics under the fermentation period between 72 h and 90 h. This result is consistent with previous reports [16,17] and suggests that the log phase is the best period for harvesting antibiotics produced by S. cavourensis YBQ59 under the optimal fermentation conditions. The CFSs of S. cavourensis YBQ59 was subjected to chemical analysis for the isolation of antimicrobial compounds (Table 1).…”
Section: Kinetic Of Fermentation Processsupporting
confidence: 90%
“…The antibiotic biosynthesis of S. cavourensis YBQ59 was observed after 18 h and the antimicrobial activity against MRSE and S. Typhimurium was dramatically increased within 42 h, then slowly increased and reached a peak located between 72 h and 78 h (inhibition zones > 34.0 mm). The antimicrobial activity was stable until 90 h and then slightly decreased after 120 h. Thus, S. cavourensis YBQ59 produced a highest yield of antibiotics under the fermentation period between 72 h and 90 h. This result is consistent with previous reports [16,17] and suggests that the log phase is the best period for harvesting antibiotics produced by S. cavourensis YBQ59 under the optimal fermentation conditions. The CFSs of S. cavourensis YBQ59 was subjected to chemical analysis for the isolation of antimicrobial compounds (Table 1).…”
Section: Kinetic Of Fermentation Processsupporting
confidence: 90%
“…AS4. Another study by Abdelghani [ 49 ] also reported that malt extract concentration of 1.0% (w/v) showed maximum antibacterial yield in S. albovinaceus . A study of cell biomass and antibacterial activity of all isolates showed a positive correlation, which was the optimum antibacterial activity found in the incubation period of days 9 to 11 or when the growth reached the stationary phase (maximum cell biomass).…”
Section: Discussionmentioning
confidence: 99%
“…KADIRI & al [30]), fructose (S.N. KUMAR & al [20]), and mannitol (T. ABDELGHANI & al [31]) have been reported to be suitable for the activity of antibiotic substances in different microorganisms. These different results shows that the optimal carbon source must be identified for maximal yield of the antibiotic of interest in different bacteria.…”
Section: Resultsmentioning
confidence: 99%